Analisis Metakognitif Siswa pada Proses Berpikir Kritis dalam Menyelesaikan Soal Matematis dengan Model PBL - Dimas Pambudhi (Departement of Mathematics Education, 2024)
This research is based on the low mathematical critical thinking skills of senior high school students. This study aims to determine the effectiveness of the metacognitive-based problem-based learning model in improving students' mathematical critical thinking skills. This research is a quasi experimental research with pre test and post test control group design. The research subjects were students of class XII senior high school in Metro City which consisted of an experimental class and a control class. The data collection technique used a test technique in the form of 5 essay questions.The instrument used has met the feasible criteria based on validity, reliability, difference power, and difficulty index. Data analysis using t-test data n-gain. Based on calculations using SPSS 21, the conclusion is that the metacognitive-based problem-based learning model is effective in improving students' critical thinking skills.